Neonatal Death in Women with Severe Preeclampsia Receiving Conservative Management: Literature Review - Intan Dewi Angia Sari; Muhammad Ilham Aldika Akbar; Atika Atika (Rifa'Institute, 2022)
Introduction: In developing countries that still have places with inadequate supporting facilities, equipment and limited trained personnel, infants less than 37 weeks may still be at high risk for severe complications and even death if active management or termination is carried out, so conservative care is recommended. Object: The aim of this study was to analyze the perinatal outcome of neonatal mortality in women with severe preeclampsia who received conservative management. Method: This study uses a literature review method which includes searching for articles in electroncic research journal databases. Search articles using Scopus and Google Scholar with no year limit. The keywords used in the search were Preeclampsia, Conservative Management, Expectative Management, and Perinatal Outcomes. A total of 637 articles were obtained, and six articles were analyzed based on the research setting, design study, samples characteristics, and research results for each article. Results and Discussion: of this study are conservative management of women with severe preeclampsia can reduce neonatal mortality rates in care in developed countries, but still shows high rates of care in developing countries. Conclusion: of the results, this study indicate that conservative management can improve maternal outcomes in the form of neonatal mortality in developed countries